Competencies And Work Performance Of Public Sector Auditors In Iraq: The Case Of Federal Board Of Supreme Audit - Hasan, Fayyadh Marwah Jawad Abd (2022)
The role of internal auditors is of high importance in the developing countries’ public sector as it involves providing independent and objective assurance and consultancy that can add value to public sector organizations. However, increased fraudulent and corruption activities within public sector organizations, particularly in developing countries such as Iraq, have elevated doubts regarding the effectiveness of the audit function. The Federal Board of Supreme Audit (FBSA) is Iraq’s leading authority to monitor the public sector institutions’ transparency, and conduct audits to evaluate the establishment and effectiveness of corporate governance within public sector organizations. Of late, the FBSA has faced challenges in terms of internal auditors’ performance which results in low confidence and trust of the public. The increased cases of fraud and corruption in the public sector of Iraq demand enhancement of FBSA internal auditors’ performance. Therefore, the key objective of the study is to examine the relationship between key influential internal auditors’ competencies, such as knowledge, effective internal communication, task self-efficacy, and computer self-efficacy, and internal auditors’ performance, such as task performance, contextual performance, and adaptive performance of internal auditors working in the FBSA, Iraq. The model of the study is underpinned by the social cognitive theory. The study also examined the moderating role of proactive personality on the relationship between internal auditors’ competencies and their performance.